Study on esthetic appearance of reconstructed pinna in microtia - Gopalan, G.; Rajendran, M. K.; Shankar, R. (International Surgery Journal, 2018)
Background: The normal external ear is a complex three-dimensional structure and, as such, reconstruction of the ear is a demanding undertaking. A new era in ear reconstruction began in 1959 when Tanzer introduced his multistage autologous rib cartilage technique and it gained wide acceptance from the surgeons. The aim of the present study was reconstruction of pinna in microtia cases using esthetic component and to study its surgical outcome. Methods: A prospective longitudinal study was conducted in the department of plastic, reconstructive and facio-maxillary surgery, Government Mohan Kumaramangalam Medical College, Salem, for a period of 2 years. A total of 26 patients with microtia were included in our study. The reconstruction of microtia was done by the following steps; a. first stage – removal of the rib cartilage and framework implantation; b. second stage - rotation of the ear lobule by Z plasty incision; c. third stage– creation of cephaloauricular sulcus; d. fourth stage - tragus construction and concha excavation. All the socio-demographic details and the clinical parameters related to the reconstructed ear were measured and tabulated. Results: The mean age of the study subjects was 14.3 years with a male: female ratio of 2:1. Based on the Tanzer classification all the patients were either in grade IIA or grade III of microtia with 35% of the patients had the hearing loss exceeding 40db. The mean length, breadth, degree of protrusion and degree of inclination of the reconstructed ear were 58.5mm, 34.6mm, 25o and 13o respectively. The most common complication reported in present study subjects was malposition of the reconstructed pinna (21.7%) followed by hematoma infection (8.6%) and hidden helix. Post-operatively the mean hearing loss was only 25db. Conclusions: The esthetic results of each of these techniques can be excellent when performed by an experienced surgeon in appropriately selected patients.